World History : an Introduction. - Vanhaute, Eric (Taylor and Francis, 2013)
World History: An Introduction provides readers with the knowledge and tools necessary to understand the global historical perspective and how it can be used to shed light on both our past and our present. A concise and original guide to the concepts, methods, debates and contents of world history, it combines a thematic approach with a clear and ambitious focus. Each chapter traces connections with the past and the present to explore major questions in world history: How did humans evolve from an endangered species to the most successful of them all?